2018
DOI: 10.1021/acsnano.8b01957
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Piezotronic Transistors with 2 nm Channel Lengths

Abstract: Because silicon transistors are rapidly approaching their scaling limit due to short-channel effects, alternative technologies are urgently needed for next-generation electronics. Here, we demonstrate ultrathin ZnO piezotronic transistors with a ∼2 nm channel length using inner-crystal self-generated out-of-plane piezopotential as the gate voltage to control the carrier transport. This design removes the need for external gate electrodes that are challenging at nanometer scale. These ultrathin devices exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 38 publications
1
69
0
1
Order By: Relevance
“…The insets represent the statistical distributions of piezoresponse amplitude variations of the GaPO 4 sheet and the substrate. The statistical distributions of the piezoresponse amplitude variations provide the opportunity to characterise the overall effective piezoelectric constant ( d eff 33 ) for the entire flake area 11 . From the piezoresponse amplitude, we characterise d eff 33 of GaPO 4 sheets quantitatively 5 , 44 46 (details concerning the d eff 33 calculation are provided in the method section).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insets represent the statistical distributions of piezoresponse amplitude variations of the GaPO 4 sheet and the substrate. The statistical distributions of the piezoresponse amplitude variations provide the opportunity to characterise the overall effective piezoelectric constant ( d eff 33 ) for the entire flake area 11 . From the piezoresponse amplitude, we characterise d eff 33 of GaPO 4 sheets quantitatively 5 , 44 46 (details concerning the d eff 33 calculation are provided in the method section).…”
Section: Resultsmentioning
confidence: 99%
“…The separation of flexoelectric and piezoelectric components of d 33 is also challenging 10 . The very recent report on the piezoelectricity of 2D ZnO provides an example of a 2D material with a large out-of-plane piezoelectric coefficient, still with lateral dimensions not exceeding several hundred microns and this does not rely on a surface synthesis processes 11 . Currently, the exploration of 2D piezoelectric materials is restricted to comparatively low temperatures, and the development of 2D materials which are able to function at elevated temperatures is still not emphasised due to the commonly observed high temperature induced instability of the piezoelectric properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] In particular, Wang et al have reported a series of nano-ZnO-based films, nanowires, and nanorod arrays, whose piezoelectric polarizationinduced built-in electric fields can promote carrier recombination and separation improving quantum efficiency and photocatalytic activity, which can be applied in nanogenerators, photocatalysis technology, flexible electronic skins, etc. [12][13][14][15][16] Furthermore, the spontaneous polarization of ferroelectrics can be switched in response to an external electric field, making them attractive for wide applications of ferroelectric memory, temperature sensing, energy harvesting, and optoelectronic devices. [17][18][19] Multiaxial ferroelectrics with multiple equivalent polarization directions are highly preferred for such applications because more equivalent ferroelectric axes allow random spontaneous polarization vectors to be oriented along the electric field to achieve reversible switching between multiple directions, and the piezoelectric effects can also occur in multiple directions to produce optimal performance.…”
Section: Introductionmentioning
confidence: 99%
“…51 Significant advances have also been achieved in studying piezoelectricity and the piezotronic effect in various 2D materials. [52][53][54][55][56][57][58][59][60][61] The study of piezoelectricity and piezotronic effects in 2D materials is an emerging field. In their article in this issue, Liu et al summarize the progress made in related fields.…”
Section: Impact On 2d Materialsmentioning
confidence: 99%